2019
DOI: 10.3390/app9112362
|View full text |Cite
|
Sign up to set email alerts
|

Volatile Secondary Metabolites with Potent Antidiabetic Activity from the Roots of Prangos pabularia Lindl.—Computational and Experimental Investigations

Abstract: (1) Background: Almost 500 million people worldwide are suffering from diabetes. Since ancient times, humans have used medicinal plants for the treatment of diabetes. Medicinal plants continue to serve as natural sources for the discovery of antidiabetic compounds. Prangos pabularia Lindl. is a widely distributed herb with large reserves in Tajikistan. Its roots and fruits have been used in Tajik traditional medicine. To our best knowledge, there are no previously published reports concerning the antidiabetic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 44 publications
0
6
0
Order By: Relevance
“…In this regard, different studies have found plant extracts containing coumarins to exhibit antidiabetic activity [ 110 ]. Osthole containing volatile oil from roots of Prangos pabularia significantly inhibited protein tyrosine phosphatase 1B (PTP-1B) with an IC 50 value of 0.06 ± 0.01 μ g/mL [ 37 ].…”
Section: The Mechanisms Behind the Pharmacological Activities Of Natural Coumarinsmentioning
confidence: 99%
“…In this regard, different studies have found plant extracts containing coumarins to exhibit antidiabetic activity [ 110 ]. Osthole containing volatile oil from roots of Prangos pabularia significantly inhibited protein tyrosine phosphatase 1B (PTP-1B) with an IC 50 value of 0.06 ± 0.01 μ g/mL [ 37 ].…”
Section: The Mechanisms Behind the Pharmacological Activities Of Natural Coumarinsmentioning
confidence: 99%
“…The EOs derived from other Prangos species such as P. pabularia Lindl., P. peucedanifolia Fenzl., P. ferulacea , P. platychlaena and P. pabularia Lindl. have also been subject of investigations by other researchers [ 17 , 22 , 31 , 32 ].…”
Section: Resultsmentioning
confidence: 99%
“…Protein tyrosine phosphatase 1B (PTP-1B) activity was measured using the PTP-1B enzyme inhibition assay according to the literature [21,22]. The reagent pNPP (p-nitrophenyl phosphate disodium salt) was used as a substrate for the measurement of PTP-1B activity.…”
Section: Antidiaibetic Activity: Ptp-1b Enzymatic Assaymentioning
confidence: 99%